A REVIEW ON MEDICINAL PLANTS OF RAJASTHAN HAVING ANTIDIABETIC ACTIVITY - Mathur, Charuta; Rs, Gupta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Diabetes is one of the most common chronic diseases in nearly all countries, and continuously increasing in numbers and significance, as changing lifestyles lead to reduced physical activity. Diabetes is the leading cause of blindness, renal failure, and lower limb amputation. Diabetes is also now one of the leading causes of death, largely because of a markedly increased risk of coronary heart disease and stroke. Due to the existing synthetic drugs have many limitations, the medicine from plants is drawing ever-increasing attention worldwide, due to their low toxicity and few side effects. The present review is providing data of some important medicinal plants species possessing antihyperglycemic and antidiabetic activity. It would provide a handbook for the research related to diabetes. Further, efforts should be made to implement these plants based drugs in clinical trials.